Modeling of AMg6 alloy recrystallization in the forged layer during the overlay welding of a material in the process of hybrid additive manufacturing - Salikhova, Nelli Kamilevna; Dudin, Dmitriy Sergeyevich; Keller, Il’ya Ernstovich; Oskolkov, Aleksandr Andreyevich; Kazantsev, Aleksandr Vladimirovich; Trushnikov, Dmitriy Nikolayevich (Computational Continuum Mechanics, 2022)
The regularities of static recrystallization during the welding of metal layer over the face of a prismatic specimen pretreated by plastic deformation are studied. This problem is of interest in selecting the rational parameters for the process of hybrid additive manufacturing of light and high-strength linear elements of segmented structures made of aluminum-magnesium alloys via layer-by-layer forging with a pneumatic hammer. For this purpose, the two independent problems of the one-sided forging of a prismatic specimen and temperature evolution during the plasma-arc welding of a layer over the same specimen are solved numerically. The fields of accumulated deformations and the history of temperature changes in the specimen are used to calculate the volume fraction of statically recrystallized material in the work-hardened layer under the influence of a thermal cycle temperature. The forging calculation was performed based on the LS-DYNA® package, the thermal problem was solved in Comsol Multiphysics®, and the fraction of recrystallized material was calculated by making use of the Wolfram Mathematica system. In the numerical model, the impact of the pneumatic hammer was estimated by means of a strain-gauged steel target, and then was verified by evaluating the distortions of the cross-section of the forged bar made of AMg6 alloy measured in the experiment. The thermal effect was calculated taking into account the PI controller, which automatically controls the overlaying process in the hybrid additive manufacturing plant. The volume fraction of a statically recrystallized material was calculated using Avrami's law and data on the dependence of the time of 50% transformation of the material on the accumulated deformation and the temperature taken from the literature on aluminum-magnesium alloy 5083, which is  similar to AMg6. The model predicts a high sensitivity of the fraction of recrystallized material to previous plastic deformation and to the maximum temperature in the thermal cycle of overlay welding, and therefore a more localized boundary layer of recrystallized material compared to the boundary layer in plastic deformation. The results of calculation demonstrate the effectiveness of layer-by-layer pressure shaping strategies for providing deep-layer plastic deformation. In terms of the degree of recrystallization, the use of rational modes of overlay welding and forging can ensure the synthesis of products with high strength and ductility characteristics in hybrid additive manufacturing processes.
Keywords: additive manufacturing; layer-by-layer forging; static recrystallization; aluminum-magnesium alloys; numerical calculation; experimental confirmation